2022
DOI: 10.1029/2022ea002243
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing ExoMars Rover Remote Sensing Multispectral Science: Cross‐Rover Comparison Using Laboratory and Orbital Data

Abstract: Multispectral imaging instruments have been core payload components of Mars lander and rover missions for several decades. In order to place into context the future performance of the ExoMars Rosalind Franklin rover, we have carried out a detailed analysis of the spectral performance of three visible and near‐infrared (VNIR) multispectral instruments. We have determined the root mean square error (RMSE) between the expected multispectral sampling of the instruments and high‐resolution spectral reflectance data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 76 publications
(135 reference statements)
0
3
0
Order By: Relevance
“…Grindrod et al. (2022) showed that Mastcam‐Z indeed has improved performance over Mastcam in simulations of both instruments' spectral responses compared to laboratory spectral libraries and Mars orbital hyperspectral data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Grindrod et al. (2022) showed that Mastcam‐Z indeed has improved performance over Mastcam in simulations of both instruments' spectral responses compared to laboratory spectral libraries and Mars orbital hyperspectral data.…”
Section: Methodsmentioning
confidence: 99%
“…At 978 nm, Mastcam-Z's R5 filter was selected to help capture narrow absorptions due to H 2 O and/or OH between 950 and 1,000 nm in hydrated minerals (e.g., Rice et al, 2010). Grindrod et al (2022) showed that Mastcam-Z indeed has Bell et al (2021) improved performance over Mastcam in simulations of both instruments' spectral responses compared to laboratory spectral libraries and Mars orbital hyperspectral data.…”
Section: Mastcam-z Instrument and Calibrationmentioning
confidence: 99%
“…All CRISM data are available through the NASA PDS Geosciences Node CRISM Archive (https://pds-geosciences.wustl.edu/missions/mro/crism.htm). Our derived spectral library and CRISM data results are available at the Figshare Archive (Grindrod, 2022).…”
Section: Data Availability Statementmentioning
confidence: 99%